Action Verba of "Memeleng" in Sasaknese: A Metalanguage Approach - Rahman, Bohri (Lingual Journal of Language and Culture; Vol 2 No 2 (2016), 2016)
In Sasak language , memeleng 'cut' has several forms such as the following variations: gecok , melekés , mépés , ngawas , beréngge , munggel , nyacak , ngawis : the meaning of memeleng in the corpus represents a transitive verb of prototype. This selection is intended to provide a brief overview of the semantic structure. Lexicon memeleng ‘cutting' describes the semantic structure of the sub - component" X doing something", "something bad happened" and "X do something", "something good happens." Lexicon with each variation do the concepts of representations. The verb of memeleng ‘cut ' the mapping component "X did something to Y" because" something happened to Y". Memeleng lexicon based on the tools, motion model, an entity that is subject to section treatment and final results are expected to be achieved.
Keywords: Action Of Verb, Sasaknese, Natural Semantic Metalanguage.